The legacy of pregnancy: Elite athletes and women in arduous occupations - Jackson, T.; Bostock, E. L.; Hassan, A.; Greeves, J. P.; Sale, C.; Elliot-Sale, K. J. (Exercise and Sport Sciences Reviews, 2022)
Best-practice guidance and management of pregnant and postpartum elite athletes and women in arduous occupations is limited by the lack of high-quality evidence available within these populations. We have summarized the adaptations and implications of pregnancy and childbirth, proposed a novel integrative concept to address these changes, and made recommendations to progress research in this area.